(untitled) (Bangladesh Medical Journal, 2016)
Renal stone or urolithiasis is the third most common disease of the urinary tract. ESWL has become the preferred treatment for renal calculi of <2 cm in diameter except in lower calyx. CT with non enhancement by contrast medium has long been used clinically to evaluate substance density in Hounsfield units (HU) to distinguish calculi from calci_cations, tumors and blood clots. Present study was conducted to evaluate effectiveness of ESWL on the basis of stone density as measured by CT scan in patients with renal stone. This hospital based cross sectional study was conducted from April, 2014 to September, 2015 in the Department of Radiology & Imaging and Department of Urology, BSMMU. Sixty patients presented with renal stone with an age group of 18 years and above in both sexes who were attended in the OPD were included as study population. Patients were divided into two groups based on HU: patients having HU<900 were belonged to Group-A and HU?900 were belonged to Group-B. Mean (SD) stone density among the respondents in Group A was 717 (76) HU and in Group B was 1091 (99) HU. Mean (SD) shockwaves needed in Group A and Group B were 2590 (223) and 3000 (132) respectively. In group A, 10 (38.5%), 13 (50.0%) and 3 (11.5%) patients needed 1, 2 and 3 session respectively for complete clearance of stone whereas in group B, 1 (11.1%), 3 (33.3%) and 5 (55.6%) patients needed 1, 2 and 3 session respectively for complete clearance of stone. This study concluded that Hounsfield units (HUs) measurement of urinary calculi on pre-treatment non-contrast CT predicts the stone fragmentation rate after extracorporeal shockwave lithotripsy (ESWL). Bangladesh Med J. 2016 May; 45 (2): 94-97